The Role of Pentahelix in Flood Disaster Risk Reduction in Cirebon City to Achieve Regional Security - Rivaldy, Mohammad; Sutisna, Sobar; Puto, Robertus Anugerah Purwoko; Kurniadi, Anwar; Kusuma, Kusuma; Wilopo, Wilopo (MOVE: Journal of Community Service and Engagement, 2025)
Massive flooding in Cirebon City poses a significant threat to regional security, requiring a collaborative disaster risk reduction (DRR) approach. This study examines the Pentahelix model's role and effectiveness, which includes government, academics, businesses, communities, and media, in managing flood risks. Using a qualitative case study, researchers gathered data from the Cirebon City Regional Disaster Management Agency (BPBD) and other key actors through in-depth interviews and participant observation. The findings show that each Pentahelix actor plays a unique and complementary role, although challenges in coordination still exist. Effective initiatives, such as the "Kota Cinta" program, have been implemented to boost local preparedness. The research emphasizes the critical role of media in disseminating information and mobilizing the public, an aspect often overlooked in previous collaborative models. Ultimately, the study concludes that the Pentahelix model is effective in building flood DRR capacity and enhancing regional security through inclusive and sustainable community engagement.